Practices in the purchase of casual streetwear by a selected group of government employees - Go, Ruvina M.
The objectives of the study were 1) to determine the clothing buying practices of women government employees, 2) to determine the relationship of age, civil status, and monthly income to their buying practices, and 3) to determine the types of apparel most commonly bought. It was hypothesized that age, civil status and monthly income have no significant relationship to clothing buying practices. The study was limited to forty-seven (47) women government employees in the accounting division of the Commission on Audit at Quezon City. The majority of the subjects were relatively young (23 to 31 years old). A survey questionnaire was used to find out the employees' clothing purchase practices. Ranking, mean, percentages and chi-square were used in the statistical treatment of data. The findings revealed that age had a significant relationship to their buying practices, and that they considered the quality and appearance of their clothing purchases more than the factors of price, care and approval of their friends.Monthly income and civil status was not significantly related to their clothing purchases. Other findings revealed that T-shirts are the most commonly brought apparel by the subjects. They patronized department stores and usually purchased their clothing needs during special occasions like Christmas. They preferred to shop in stores in Cubao and paid cash for their purchases. The results of the investigation were based on the practices of a very limited population. A larger population of government employees from different offices may give more conclusive and interesting results.